CONSERVATION LAWS AND SYMMETRY ANALYSIS OF (1+1)-DIMENSIONAL SAWADA-KOTERA EQUATION - S. R. Hejazi; E. Lashkarian (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2017)
The paper addresses an extended (1+1)-dimensional Sawada-Kotera (SK) equation. The Lie symmetry analysis leads to many plethora of solutions to the equation. The non-linear self-adjointness condition for the SK equation established and subsequently used to construct simplified independent conserved vectors. In particular, we also get conservation laws of the equation with the corresponding Lie symmetry.